2007
DOI: 10.1002/hipo.20395
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin‐8 and N‐cadherin differentially regulate pre‐ and postsynaptic development of the hippocampal mossy fiber pathway

Abstract: Cells sort into regions and groups in part by their selective surface expression of particular classic cadherins during development. In the nervous system, cadherin-based sorting can define axon tracts, restrict axonal and dendritic arbors to particular regions or layers, and may encode certain aspects of synapse specificity. The underlying model has been that afferents and their targets hold in common the expression of a particular cadherin, thereby providing a recognition code of homophilic cadherin binding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 98 publications
2
64
1
Order By: Relevance
“…2 A-F, J, and K). Because overexpression of members of the cadherin/catenin complex also promotes axonal outgrowth (22)(23)(24)(25)(26), a simple interpretation is that N-cadherin mediates activity-dependent neurite outgrowth by promoting extracellular contacts between axons and dendrites.…”
Section: Discussionmentioning
confidence: 99%
“…2 A-F, J, and K). Because overexpression of members of the cadherin/catenin complex also promotes axonal outgrowth (22)(23)(24)(25)(26), a simple interpretation is that N-cadherin mediates activity-dependent neurite outgrowth by promoting extracellular contacts between axons and dendrites.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of hippocampal slices with a peptide blocking N-cadherin prevents further dendritic elaboration and leads to dendritic retraction in CA3 neurons. 35 Expression of a construct expressing the extracellular and transmembrane domains of N-cadherin in hippocampal neurons leads to a modest increase in dendritic branching. 36 N-cadherin mediated extracellular interaction has also been implicated in activity-mediated dendritic outgrowth.…”
Section: The Cadherin-catenin Complex In Dendrite Morphogenesismentioning
confidence: 99%
“…This includes the finding that overexpression of cadherin-11 increases synapse density in cultured neurons whereas overexpression of either cadherin-13, cadherin-9, or N-cadherin does not. 51,65,68 Axons of hippocampal dentate gyrus (DG) neurons grow longer on an N-cadherin substrate compared to a cadherin-8 substrate 69 and motor neurons use differential expression of type II cadherins to sort into topographically defined motor pools. 63 It was also shown that high frequency stimulation capable of inducing long term potentiation in the medial molecular layer of the hippocampus selectively decreases cadherin-8 from this layer but does not alter N-cadherin expression.…”
Section: Differentially Expressed Cadherins In Synaptic Specificitymentioning
confidence: 99%